Phytochemical Constituents of Capsella bursa-pastoris and Their Anti-inflammatory Activity - Cha, Joon Min; Kim, Dong Hyun; Lee, Tae Hyun; Subedi, Lalita; Kim, Sun Yeou; Lee, Kang Ro (Natural product sciences, 2018)
Phytochemical investigation of 80% MeOH extract of the aerial parts of Capsella bursa-pastoris yielded fourteen compounds (1 - 14). The structures of the compounds were elucidated by spectroscopic methods to be methyl-1-thio-b-D-glucopyranosyl disulfide (1), 10-methylsulphinyl-decanenitrile (2), 11-methyl-sulphinyl-undecanenitrile (3), 1-O-(lauroyl)glycerol (4), phytene-1, 2-diol (5), (3S,5R,6S,7E)-5,6-epoxy-3-hydroxy-7-megastigmen-9-one (6), loliolide (7), b-sitosterol (8), 3-hydroxy-1-(4-hydroxy-3-methoxyphenyl)-1-propanone (9), 1-feruloyl-b-D-glucopyranoside (10), pinoresinol-4'-O-b-D-glucopyranoside (11), luteolin (12), quercetin-3-O-b-D-glucopyranoside (13), and luteolin 6-C-b-glucopyranoside (14). Although compound 1 was reported as synthetic compound, 1 was first isolated from natural source. NMR spectral data assignments of 1, 2 and 3 were reported for the first time, and compounds 1 - 14 were for the first time reported from this plant source. The anti-inflammatory effects of 1 - 14 were evaluated in lipopolysaccharide (LPS)-stimulated murine microglia BV-2 cells. Compounds 12 exhibited strong inhibitory effects on nitric oxide production in LPS-activated BV-2 cells with IC50 values of 9.70 mM. KCI Citation Count: 1